Characterization of the cell−Fe mineral aggregate from nitrogen removal employing ferrous and its adsorption features to heavy metal. (10th July 2017) - Li, Yingfen; Long, Xinxian; Chong, Yunxiao; Yu, Guangwei; Huang, Zhujian
Abstract: Microbial nitrate-dependent anaerobic Fe(II)-oxidizing(NAFO), capable of coupling reduction of nitrate and oxidation of ferrous iron, has become a new approach for the removal of nitrate in wastewater. The cell−Fe mineral aggregate formed in NAFO reaction would become bio-solid of the treatment, which was suggested potential to bind heavy metals in wastewater. As the first time, the characteristic of the cell−Fe mineral aggregate, which was gained in batch microbiological NAFO reaction using NAFO enrichment culture in laboratory, was revealed in this work. And its adsorption ability for cadmium, lead, nickel and zinc in solution was verified. Scanning electron microscope (SEM) showed that it contained mainly iron oxide particles and bacteria cell. And the arrangement between iron oxide particles and cells was irregular. Most of iron oxide particles flocculated together outside the cell, while a little deposited on surface of cell. Breunauer-Emmett-Teller (BET) adsorption analysis indicated these aggregates were typical mesoporous material. Fourier transform infrared (FITR) revealed that phosphate and organic functional group including carboxylate anion and amide distributed on the surface of the aggregates. In addition, the cell−Fe mineral aggregate exhibited strong ability of binding cadmium, lead, nickel and zinc which were in low concentration scope. Kinetic of adsorption to each heavy metal fitted well the pseudo second-order model. The results of FITR and X-ray photoelectron spectroscope (XPS) on the cell−Fe mineral aggregate before and after adsorption indicated that iron oxide, phosphate and organic functional groups on the surface all made significant contributions to the adsorption. Iron oxide, carboxylate anion and amide played an important role in adsorption of all heavy metals, while phosphate mainly responded to the binding of Cd, Ni and Zn. All these results confirmed cell−Fe mineral aggregate from NAFO reaction was an effective recyclable material for heavy metal-polluted wastewater treatment. Highlights: The cell−Fe mineral aggregate contained mainly iron oxide particles and bacteria cell. Phosphate and organic functional group distributed on the surface of the aggregates. The cell−Fe mineral aggregates exhibited strong ability of binding cadmium, lead, nickel and zinc. Iron oxide, phosphate and organic functional groups had contribution to the adsorption.